Enhancing frameworks for assuring the quality of learning and teaching in university offshore education programs : final report. - O'Donoghue, Thomas; Chapman, Anne; Pyvis, David; Aspland, Tania; Melville, Ian (Australian Learning and Teaching Council, 2010)
The project which is the substance of this report was prompted by the need for a national quality strategy that enhances the quality of teaching and learning in offshore education programs of Australian universities. It addresses three objectives: to compile a database of international and national policy documents, empirical studies and quality assurance frameworks relating to such programs; to conduct an empirically-based qualitative study of the perspectives of key academic stakeholders on the delivery of such programs across the range of models which operate; and to develop a framework to guide those concerned with: quality assurance for transnational teaching by Australian universities; and conducting professional development programs for those working transnationally. [Executive summary, ed]